Towards a Quantitative Single Particle Characterization by Super Resolution Microscopy: From Virus Structures to Antivirals Design - Arista-Romero, Maria; Pujals, Silvia; Albertazzi, Lorenzo (Frontiers in Bioengineering and Biotechnology, 2021)
In these years the COVID19 pandemic showed all the potential of viruses to threat our society. The characterization of viral structures and the identification of key proteins involved in each step of the cycle of infection are crucial to develop treatments. However, the small size of viruses, invisible under conventional fluorescence microscopy, make difficult to study the organization of those protein clusters within the viral particle. Super-resolution microscopy has burst in the last years positioning as the perfect technique to characterize virus and study the viral infection on cells, breaking the diffraction limit by achieving resolutions up to 10 nm using conventional probes such as fluorescent dyes and proteins. There are several super-resolution methods available and the selection of the right one it is crucial to study in detail all steps involved in the viral infection, quantifying and creating models of infection for relevant viruses such as HIV-1, Influenza, herpesvirus or SARS-CoV-1. Here we review the use of super-resolution microscopy to study all steps involved in the viral infection and antiviral design. In light of the threat of new viruses, these studies could inspire future assays to unveil the viral mechanism of emerging viruses and further develop successful antivirals against them